2019
DOI: 10.1111/ics.12569
|View full text |Cite
|
Sign up to set email alerts
|

Age, lifestyle and self‐perceptions of hair: Is there an association with hair diameter and tensile properties?

Abstract: Objective To determine the association of age, lifestyle habits and the self‐perception of hair condition with the objectively measured physical properties of hair in Caucasian females with brown hair. Methods Hair biophysical properties, lifestyle habits data and self‐perceptions of hair condition were collected on 110 Caucasian females with brown hair ranging in age from 17 to 78. Hair diameter (cross‐sectional area) and tensile properties (elastic modulus, break strength and break extension) were measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…Another study reported a decline in hair fiber diameter with age and that seemed to accelerate around the age of 40. 25 They reported that hair thickness tended to increase until the 20 s-40 s and decrease after the 50 s. This discrepancy with our results could be due to the difference in the age of the included subjects, as our subjects ranged from 13 to 58 years with only three subjects aged above 50. However, in the above study the subjects were aged from 10 to 69 years.…”
Section: Ta B L E 7 Analysis Of Male Hair Parameters In Smokers and N...contrasting
confidence: 99%
See 1 more Smart Citation
“…Another study reported a decline in hair fiber diameter with age and that seemed to accelerate around the age of 40. 25 They reported that hair thickness tended to increase until the 20 s-40 s and decrease after the 50 s. This discrepancy with our results could be due to the difference in the age of the included subjects, as our subjects ranged from 13 to 58 years with only three subjects aged above 50. However, in the above study the subjects were aged from 10 to 69 years.…”
Section: Ta B L E 7 Analysis Of Male Hair Parameters In Smokers and N...contrasting
confidence: 99%
“…These findings were similar to those reported by Kim et al on Koreans, 22 Tajima et al 23 on Japanese, and Robbins et al 24 on Caucasians. Another study reported a decline in hair fiber diameter with age and that seemed to accelerate around the age of 40 25 …”
Section: Discussionmentioning
confidence: 98%